Determination of the inter-repair cycle of production boreholes for underground uranium leaching - Yu. А. Arsentiev; A. P. Nazarov; N. V. Soloviev; D. А. Ivanov; А. G. Ivanov (Известия высших учебных заведений: Геология и разведка, 2024)
Introduction. The operation of technological wells for underground leaching of metals inevitably leads to a decrease in their design productivity, which is accompanied by an increase in the development time of deposits. This paper shows the impact of the timeliness of repair and restoration work on the efficiency of metal mining, and also substantiates the calculated indicators for determining the duration of repair and restoration work cycles between repairs.Target. This work is an attempt to analytically develop the main indicator of the duration of the overhaul cycle of the operation of technological wells to determine the frequency of repair and restoration work (RVR) depending on the intensity of the decline in the productivity of borehole in situ leaching (IIL) wells and the coefficient for selecting an effective type of complexes of technical means and technological methods for carrying out RVR.Materials and methods. This work makes it possible to solve the above problems by approximating the exponential pattern of changes in the productivity of a technological well over time by a linear function.Results. The specified methodological approach made it possible to obtain the main and derivative indicators: Тм — the duration of the MRC of a technological well, kв  — the indicator of restoration of a technological well, kэ  — an indicator for choosing an effective type of RWR and to formulate methodological provisions for justifying the frequency of performing RWR of technological wells of SPV uranium to restore them as designed, and the permissible maximum performance.Conclusion. The resulting dependencies have a simple form and can be used by the linear personnel of the RVR and DPR (production of productive solutions).